COVID-19: Limiting the Risks for Eye Care Professionals. (3rd July 2020) - Sadhu, Soumen; Agrawal, Rupesh; Pyare, Richa; Pavesio, Carlos; Zierhut, Manfred; Khatri, Anadi; Smith, Justine R.; de Smet, Marc D; Biswas, Jyotirmay
ABSTRACT: After the outbreak of the disease COVID-19, it has reached pandemic proportions within a very short time. It is mainly transmitted human-to-human through direct contact with secretions from an infected person or through inhalation of droplets containing SARS-CoV-2. It is controversial whether the virus may be transmitted via tears. Exposed ocular surface can serve as a gateway in transmission and acquiring respiratory diseases. Considering the reported cases on healthcare workers indicating nosocomial transmission and the anatomical and physiological aspects it is perceived that ophthalmic healthcare professionals are at higher risk of contracting the virus by virtue of their job. In this narrative review we discuss current evidence around detection of SARS-CoV-2 in human tears and forms of transmissions reported to date. We also provide a comprehensive approach that may be implemented in an ophthalmic care facility to protect healthcare personnel, as well as patients, from contracting the virus.